The Dark Side of Meritocratic Beliefs: Is Believing in Meritocracy Detrimental to Individuals from Low Socioeconomic Backgrounds? - García-Sierra, Alicia (Social justice research, 2023)
Individuals’ perceptions of how the path toward success is built might affect their choices and behaviors. This study examines whether holding meritocratic beliefs has heterogeneous effects on the long-term socioeconomic outcomes of individuals from different SES. I argue that, when the hurdles faced by the less privileged groups during their educational and labor market trajectories clash with their meritocratic beliefs, the generated frustration and low self-efficacy will affect their decisions and their performance, which eventually may impact their socioeconomic outcomes. Using German longitudinal data and siblings' fixed effects, results reveal that individuals from low socioeconomic backgrounds who hold strong meritocratic beliefs during their adolescence are more likely to have a precarious work situation when they are adults, as well as less likely to be fully working. This effect is reversed or non-existent for those from high socioeconomic status. These results open new paths to explore the crucial effect that societal discourses praising the meritocratic ideal could have on individuals from more deprived socioeconomic backgrounds.